KLASIFIKASI JENIS-JENIS BISNIS E-COMMERCE DI INDONESIA - Mahir Pradana (Trunojoyo University of Madura, 2015)
Indonesian people, especially those living in urban areas, are inseparable from the Internet, because almost all activities involve internet and information technology. Thus, no wonder if the internet has become a basic requirement for some people, especially those who use the internet for business purposes (e-commerce). E-commerce is defined as the process of buying, selling, transferring or exchanging products, services or information through computer networks via the internet. With e-commerce as business activities, the company can expand and reach consumers more easily. They can also process conventional transactions to be more modern with the availability of online transactions. Collective society, for example in Asian countries such as India and Indonesia, depend more social interaction than those who live in the individualistic-oriented community. Connecting the characteristics of Indonesian society with the types of business interactions, more or less variations of e-commerce business in Indonesia can be divided into several types, namely listings, shopping mall, marketplace, online stores, online stores on social media and crowdsourcing / crowdfunding. This article aims to discuss more about the types of business e-commerce as well as the development of the underlying information systems theory